INDEKS GLIKEMIK, BEBAN GLIKEMIK DAN AKTIVITAS ANTIOKSIDAN JUS KAWISTA (LIMONIAACIDISSIMA) SEBAGAI MINUMAN FUNGSIONAL PENGONTROL KADAR GULA DARAH - Inayah Inayah; Metty Metty; Tri Mei Khasana (Universitas Respati Yogyakarta, 2020)
Glycemic Index, Glycemic Load and Antioxidant Activity Kawista Juice (Limoniaacidissima) as a functional drink to control blood sugar levelsBackground: Diabetes Mellitus is the third cause of death after stroke and heart disease in 2014. The prevalence of Diabetes Mellitus according to Basic Health Research in 2013 is almost double compared to that in 200. Diabetes sufferers in Indonesia will continue to increase from 8.4 million in the year 2000 to 21.3 million in 2030. This situation requires serious handling and attention from all parties, especially those related to nutrition and food. One of the measures related to nutrition and food is the provision of foods that have a low glycemic index, high fiber, and oxidant activity. Kawista fruit (Limonia acidissima) is one type of fruit that is currently becoming rare in Indonesia. Kawista fruit is believed to have many benefits with glucose content as a source of energy and antioxidants. Kawista fruit is believed to be used to cure tumors, asthma, treat wounds, cardiovascular disease, cardiovascular circulation and hepatitis. Flavonoids, glycosides, saponins and tannins are also contained in this fruit. Objective: To determine the glycemic index, glycemic load, and antioxidant activity of Kawista fruit juice. Methods: This study is quasi-experimental. Measurement of the glycemic index, the glycemic load was carried out on respondents aged 20-30 years with normal nutritional status. Respondents were checked for fasting blood sugar levels to determine the sugar levels in their blood. The intervention was carried out for 2 consecutive days. On the 1st day, the respondents were given a glucose load of 25gr and measured their blood sugar levels at 0, 30, 60, 90, and 120 minutes. On the second day of the intervention, respondents were given 330 ml of Kawista fruit juice which was then measured for blood sugar levels. at minutes 0.30, 60.90, and 120. Results: The levels of antioxidants were checked in the Food Technology Laboratory of UGM Yogyakarta. The glycemic index of Kawista Juice from this study is in a low category. The antioxidant activity is known to be 47%. Conclusion: Kawista juice glycemic index is included in the low category with antioxidant activity of 47%.